Ecosystem assessment of mountain ash forest in the Central Highlands of Victoria, south‐eastern Australia. (25th September 2014) - Burns, Emma L.; Lindenmayer, David B.; Stein, John; Blanchard, Wade; McBurney, Lachlan; Blair, David; Banks, Sam C.
Abstract: We applied an ecosystem risk assessment to the mountain ash forest ecosystem of the Central Highlands of Victoria (hereafter 'mountain ash forest'), south‐eastern Australia, using the IUCN Red List of Ecosystems criteria. Using this methodology, we quantified: (i) key aspects of the ecosystem's historical, current and future decline in spatial distribution; (ii) the extent of occurrence and area of occupancy for the mountain ash ecosystem; and (iii) the decline in key abiotic and biotic processes and features for historical, current and future time periods. We developed a probabilistic model of tree growth stages to estimate the risk of ecosystem collapse within 50 to 100 years in the mountain ash forest. There was uncertainty in our estimates of risk under the various IUCN criteria, with two sub‐criteria being categorized as 'Data Deficient'. Our overall ranking of risk of collapse for the ecosystem was Critically Endangered. We are confident that this risk category is appropriate because all 39 scenarios modelled indicated a ≥92% chance of ecosystem collapse by 2067. Our findings highlight the important need for timely policy reform to facilitate improved management of the mountain ash ecosystem in Victoria. In particular, there needs to be greater protection of remaining areas of unburned forest, and restoration activities in parts of the forest estate. Implementation of these strategies will require a significant reduction in logging pressure on the mountain ash ecosystem.